BRAZIL-CHINA ENVIRONMENTAL AGENDA AS AN AUTONOMISING VECTOR - Jóhidson André Ferraz de Oliveira; Ana Silvia Andreu da Fonseca; Caroline da Costa Silva Gonçalves (Revista Tempo do Mundo, 2023)
This article deals with some emerging aspects in the discussion on climate at a global level, with regard to the link between Brazil and China, the limits and gains for a global environmental agenda, mainly in relation to the energy transition. Data and reflections are provided on the potential and dilemmas of the green giant, Brazil, allied to the industrial and technological colossus, China, for the environmental agenda. Autonomy, a Latin American theory that shows there are autonomous possibilities for countries to emerge from a position of underdevelopment and dependence, forms the basis of these reflections. The current historical moment, with the shift of central power from the Western North to Asia, presents an opportunity for Brazil to establish itself at a better level on the international stage if it manages to ally itself as equitably as possible with China in green economy projects, as indicated by some agreements signed recently between the two countries. The United States and the European Community already have their own agendas – and limitations – in environmental affairs. Latin America, especially South America, and specifically Brazil, have the potential to organize and regulate a new, bolder, and more feasible energy transition agenda that goes beyond so-called green colonialism.